Teacher Education for Language Assessment and Testing: Postgraduate Program Evaluation from its Students’ Perspective - Papadima-Sophocleous, Salomi (Colombian Applied Linguistics Journal, 2022)
A review of research conducted on language assessment teacher education (TE) revealed a lack of studies focused on the participants’ perspective. This work concentrates on the evaluation of an online computer-assisted language assessment and testing (CALAT) TE program offered for four consecutive years. The research was based on a conceptual, multidimensional e-learning evaluation model. The data were obtained from 19 practicing language teachers who attended the MA in Computer-Assisted Language Learning via an online anonymous survey focused on 1) the participants’ engagement; 2) course organization, teaching mode, and materials; 3) course strengths; 4) course aspects most helpful for learning; and 5) course aspects that constituted obstacles for learning. The results indicate the participants’ positive attitude towards the course; they highlighted that their knowledge, skills, and principles had improved, as well as the constructivist instructional design and the organization, teaching modes, and materials of the course, which motivated them and involved them in active interaction and collaboration. The participants also perceived the assessment practices performed during the course in a positive way, which favored their learning and teaching practice within the classroom. The results also include some recommendations for course improvement.